(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Solanum xanthocarpum belonging to the family Solanaceae is very diffusely branched and creeping and perennial herb. The presence of thorns on stem it’s also called Kantakari. The all parts of the plants are medicinally important. The cuttings of Solanum xanthocarpun treated with IAA and IBA in different concentrations (10, 50 and 100ppm) and their effect on plant growth have studied. IBA treated cutting showed better response on plant growth as height/length, number of leaves, size of leaves, number of nodes and internodes, number of branches, number and length of root as compared to IAA treated cuttings and control.